The Harrowing Reality of Child Rights Violations in Patricia McCormick’s Sold (Research Journal of Padmakanya Multiple Campus, 2025)
Patricia McCormick’s Sold is a powerful and heart-wrenching novel that pulls back the curtain on the dark, often unseen world of human trafficking. Through its vivid portrayal of young girls trapped in a cycle of exploitation, the book exposes the brutal violations of human rights they endure, offering a painful reminder of the harsh realities that too many face in silence. The novel narrates the journey of Lakshmi, a thirteen-year-old girl from Nepal, who is deceived and sold into sexual slavery. Through a first-person, free-verse narrative, McCormick exposes the harsh conditions of forced labor, exploitation, and psychological trauma inflicted upon trafficked victims. This paper explores how Sold highlights fundamental human rights violations, including child trafficking, forced prostitution, lack of access to education, and physical and emotional abuse. By employing a human rights framework, this study critically examines the novel’s depiction of injustice and the broader implications for raising awareness and advocating change. McCormick’s work serves as a powerful tool for social consciousness, urging action against human rights abuses and reinforcing the need for global intervention.